Circular dichroism spectroscopy reveals invariant conformation of guanine runs in DNA - Kypr, Jaroslav; Vorlícková, Michaela (Biopolymers, 2002)
We demonstrate that the characteristic circular dichroism (CD) features of the parallel-stranded DNA tetraplex of d(G4), especially the strong band at 260 nm, are characteristic for the B and A forms of the antiparallel duplex of d(C4G4). Hence, this band evidently originates from intrastrand guanine-guanine stacking, which is therefore very similar in the duplex and tetraplex DNA. In addition, the same type of the CD spectrum is provided by the ordered single strand of d(GA)10. This observation suggests that the ordered single strand of d(GA)10 is stabilized by a core of guanines stacked like in the parallel tetraplex. This view is used to start the modeling of the molecular structure of the ordered d(GA)10 single strand. Our studies suggest that guanine itself is strong enough to stabilize various secondary structures of DNA, which is a property relevant to thinking about the origin and evolution of molecular replicators.
Keywords: DNA; konformace nukleové kyseliny; Dimerization; Nucleic Acid Conformation; Guanine; guanin; dimerizace; cirkulární dichroismus; Circular Dichroism